New records of the genus Whartonia (Acari, Leeuwenhoekiidae) associated with the bat Carollia perspicillata from southeastern Brazil - Paulo da Silveira; Leopoldo Bernardi; Almir Pepato (Check List, 2015)
Two species of mites belonging to the genus Whartonia Ewing, 1944, family Leeuwenhoekiidae (Womersley, 1944), were obtained from Carollia perspicillata (Linnaeus, 1758) bats from mine tunnels in the municipalities of São José da Safira and Medina, Brazil: W. (W). pachywhartoni Vercammen-Grandjean, 1966 and W. (W.) nudosetosa Wharton, 1938. A table with all Whartonia (Whartonia) species and their respective morphological characters is presented.